2022
DOI: 10.3390/fermentation8070292
|View full text |Cite
|
Sign up to set email alerts
|

Fermentation Enhances the Anti-Inflammatory and Anti-Platelet Properties of Both Bovine Dairy and Plant-Derived Dairy Alternatives

Abstract: Within the present study, the effects of fermentation on the anti-inflammatory and anti-platelet properties of both homemade and commercially purchased bovine dairy and almond, coconut, and rice-based dairy alternatives were evaluated. The extracted total lipids (TL) from homemade and commercially purchased fermented and unfermented bovine, almond, coconut, and rice-based products were further separated into their neutral lipids (NL) and polar lipids (PL) fractions by counter current distribution. The TL, PL, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…The bacterium L. acidophilus has been shown to reduce PAF-induced inflammatory response in human intestinal cells [ 133 ]. A similar investigation [ 134 ] found that fermentation increases the antithrombotic properties of bovine dairy and plant-based dairy alternative drinks. Homemade dairy alternatives prepared from almond, coconut and rice and bovine dairy milk showed significantly higher antiplatelet activity against PAF, in comparison to their non-fermented counterparts, with the rice-based drink displaying the strongest inhibitory activity.…”
Section: Antiplatelet Properties Of Polar Lipidsmentioning
confidence: 92%
“…The bacterium L. acidophilus has been shown to reduce PAF-induced inflammatory response in human intestinal cells [ 133 ]. A similar investigation [ 134 ] found that fermentation increases the antithrombotic properties of bovine dairy and plant-based dairy alternative drinks. Homemade dairy alternatives prepared from almond, coconut and rice and bovine dairy milk showed significantly higher antiplatelet activity against PAF, in comparison to their non-fermented counterparts, with the rice-based drink displaying the strongest inhibitory activity.…”
Section: Antiplatelet Properties Of Polar Lipidsmentioning
confidence: 92%
“…brevis [92,93], but a relatively high bioactive dose of one gram of CLA per day has been found to be necessary to achieve a therapeutic effect [135]. Glenn-Davi, Hurley [94] separated the lipid contents of LAB-fermented coconut, rice, and almond milk alternative products and showed a significant increase in anti-inflammatory and anti-platelet biofunctionality of the polar lipid fraction, while the total lipid content did not change consistently. A rational was provided that fermentation altered the degree of fatty acid saturation toward a more unsaturated polar lipid fraction with improved bioactive properties.…”
Section: Lipidsmentioning
confidence: 99%
“…However, the research is still at a preliminary stage to date, which necessitates the need for further study. Numerous studies have been conducted to investigate the cardioprotective properties of polar lipids such as marine and dairy-derived lipids in vitro [11][12][13][14]. These dietary polar lipids appear to inhibit platelet aggregation induced by agonists such as PAF and TRAP-6.…”
Section: Introductionmentioning
confidence: 99%
“…Ovine or sheep's milk has been noted for its many potential health benefits besides its rich nutritional content, such as its anti-inflammatory, antiplatelet, and antimicrobial properties [15,16]. The fermentation of ovine milk has been shown to further enhance its antithrombotic properties by altering the fatty acid profile of monounsaturated fatty acids (MUFA) [13,14].…”
Section: Introductionmentioning
confidence: 99%